Perceived threat predictor of calcium-rich foods in the women of premenopausal age Isfahan - Iran in 2013-2014 - Parvin Bahadoran; Marjan Hoseini; Ashraf Kazemi (Wolters Kluwer Medknow Publications, 2015)
Background: During women lives, frequently face the challenge of calcium reduction and absorption. Decreased calcium absorption followed by a decrease in estrogen at perimenopausal ages, low average per capita calcium intake among women, wrong nutritional behavior, household income reductions and make them more susceptible to osteoporosis and related complications. The aim of this study was to evaluate the relationship between the health belief model constructs and consuming calcium-rich foods in menopausal age women. Materials and Methods: This study was descriptive-correlation study. The questionnaires were completed by 210 menopausal women who had referred to health centers. The research data were analyzed using: Frequency distribution, mean score, Pearson correlation coefficients and multivariate regression. Significant level of P < 0/05 were considered. Results: The mean and standard deviation of the scores for perceived susceptibility and severity of the threats of consumption and complications of inadequate intake were respectively: (62.1 and 38.9, and 60.2 and 39.9) and (59.6 and 37.9 and 56.3 and 36.5). The relationship between the number of units of calcium intake with perceived susceptibility and severity calcium intake and complications caused by the inadequate intake of calcium were (P < 0.001, r = 0.581, r = 0.651) and (P < 0.001, r = 0.634, r = 0.567). Conclusions: The obtained results indicate that perceived threat is the prognostic factor for the intake of calcium-rich foods and the increase of perceived threat in the health promotion programs may be associated with the increase in the consumption of calcium-rich foods in the women of premenopausal age.